Development of Coaching Learning Techniques in Overcoming Language Errors in Grade VI Students at Al Bukhari Muslim Private Elementary School - Ar Saputra, Sischa Sri; Hasibuan, Ahmad Laut (International Journal of Educational Research Excellence (IJERE), 2025)
This study aims to develop coaching learning techniques to address language errors in sixth-grade students at Al Bukhari Muslim Private Elementary School for the academic year 2024-2025. The method used was Research and Development (R&D), which includes planning, development, and evaluation. The planning stage involves an initial study of common language errors occurring in sixth-grade students, as well as an analysis of student needs and characteristics. Coaching learning techniques were designed and developed based on the findings of the planning stage. In the development stage, coaching techniques are implemented in learning situations appropriate to the context of sixth-grade students. The teaching process is based on coaching principles, such as providing constructive feedback, exploring students' potential, and guiding them to identify and correct language errors. The evaluation stage was conducted to measure the effectiveness of the coaching techniques. Evaluation includes observing the learning process, analyzing test results, and collecting feedback from students and teachers regarding their learning experiences. By implementing coaching techniques, it is hoped that students will be more active in identifying and correcting language errors